Analytical research on energy harvesting systems for fluidic soft actuators. (30th January 2018) - Wang, Tao; Song, Wei; Zhu, Shiqiang
Energy consumption has significant influence on the working time of soft robots in mobile applications. Fluidic soft actuators usually release pressurized fluid to environment in retraction motion, resulting in dissipation of considerable energy, especially when the actuators are operated frequently. This article mainly explores the potential and approaches of harvesting the energy released from the actuators. First, the strain energy and pressurized energy stored in fluidic soft actuators are modeled based on elastic mechanics. Then, taking soft fiber-reinforced bending actuators as case study, the stored energy is calculated and its parametric characteristics are presented. Finally, two energy harvesting schematics as well as dynamic models are proposed and evaluated using numerical analysis. The results show that the control performance of the energy harvesting system becomes worse because of increased damping effect and its energy harvesting efficiency is only 14.2% due to the losses of energy conversion. The energy harvesting system in pneumatic form is a little more complex. However, its control performance is close to the original system and its energy harvesting efficiency reaches about 44.1%.